FUNCTIONAL ASSESSMENT METHODS IN PATIENTS WITH COMBINED INJURIES OF THE NOSE AND PARANASAL SINUSES - Bakiyeva SH.X,; Karimberdiyev B.I,; Djurayev J.A,; Soatov I.O, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  Combined  injuries  of  the  nose  and  paranasal  sinuses  represent  a significant  clinical  challenge  due  to  their  impact  on  both  anatomical  integrity  and functional status. This study aims to evaluate the effectiveness of modern functional diagnostic  methods  in  patients  with  such  injuries.  A  total  of  140  patients  were examined  using  a  комплекс  of  clinical,  instrumental,  and  functional  assessment techniques,  including  anterior  rhinoscopy,  rhinomanometry,  olfactory  testing,  and computed  tomography  (CT).  The  results  demonstrate  that  functional  diagnostic methods provide critical information for determining the severity of impairment and guiding treatment strategies. Rhinomanometry and CT imaging were found to be the most  informative  tools  for  assessing  nasal  airflow  and  structural  damage.  Early functional evaluation improves treatment outcomes and reduces complications.